TINJAUAN HUKUM ISLAM TERHADAP PEMBERDAYAAN EKONOMI MUSTAHIK ZAKAT PRODUKTIF DI BAITUL MAL KABUPATEN PIDIE JAYA - Muhammad Mahmud; Nadia Mestura (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2019)
This scientific paper discusses "Review of Islamic Law on EconomicEmpowerment Must Be Productive Zakat in the Baitul Mal of Pidie JayaRegency." To examine three fundamental problems, namely: Mechanism ofProductive Zakat Management in Pidie Jaya Baitul Mal, Impact of DistributingProductive Alms on Mustahik Economic Welfare. and Overview of Islamic LawAgainst Management of Productive Alms in Pidie Jaya's Baitul Mal. The researchaims to obtain an overview as mentioned above. Research data obtained in thefield, researchers used several methods, namely field research (Field Research),using the techniques of observation, interviews, and documentation, and libraryresearch (Library Research). The results showed that the productive managementmechanism of zakat in Baitul Mal Pidie Jaya, is a pattern of zakat managementwhereby amil provides zakat funds to mustahik in the form of qardul hasanfinancing (interest-free loans), namely: mustahik is to use the loan funds forbusiness to return some or all of the borrowed funds in a certain period of time.After the funds are returned to amil, then amil transfers the funds to othermustahik. The impact of the distribution of Productive Zakat on the economicwelfare of mustahik. With proper empowerment and allocation, zakat will be apotential source of funds that is used for public welfare for the entire community.Overview of Islamic Law on the Management of Productive Zakat in the PidieJaya Baitul Mal, is the stage of the process of distributing productive zakat tomustahik who receive zakat, this can certainly be in line with social values and theconcept of shari'ah economy which emphasizes that funds must not be idle andmust productive.